2020
DOI: 10.1021/acsomega.0c02479
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Transformation of Astaxanthin from Haematococcus pluvialis Improves Its Antioxidative and Anti-inflammatory Activities

Abstract: Astaxanthin is a strong antioxidant, but the effect of esterification on its biological activities remains unclear. Here, we chemically synthesized three forms of astaxanthin (nonesterified (Ast-N), monoesterified (Ast-mE), and diesterified (Ast-dE) forms) using esterified astaxanthin (Ast-E) in natural extract from Haematococcus pluvialis and characterized them by spectrophotometry and high-performance liquid chromatography (HPLC). Additionally, the antioxidant and anti-inflammatory act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…It was observed that pre-treating normal fibroblast cells with AST increased the cell viability in a dosedependent manner attesting its antioxidant power. Furthermore, Nagaraj, Rajaram [31] analyzed the cell viability by MTT assay with different concentrations of AST (5,10,15,20, and 25 µg/mL) to incubate at different periods. The results indicated that the AST (25 µg/mL) significantly obstructs the HepG2 cancer cell growth and induces cell apoptosis.…”
Section: Anti-proliferative Activity and Intracellular Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that pre-treating normal fibroblast cells with AST increased the cell viability in a dosedependent manner attesting its antioxidant power. Furthermore, Nagaraj, Rajaram [31] analyzed the cell viability by MTT assay with different concentrations of AST (5,10,15,20, and 25 µg/mL) to incubate at different periods. The results indicated that the AST (25 µg/mL) significantly obstructs the HepG2 cancer cell growth and induces cell apoptosis.…”
Section: Anti-proliferative Activity and Intracellular Rosmentioning
confidence: 99%
“…For biological activity, AST can significantly decrease oxidative stress and free radicals. AST has several nutraceutical and human health-promoting applications including in the anti-proliferation, anti-inflammatory, anti-cancer, and cardiovascular systems [5,[10][11][12]. With increasing demand, AST will be one of the important microalgal products in the future [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, its biological activities, such as pigmentation, ultraviolet (UV) light protection, immune response, antioxidative effects, reproductive capacity, and stress tolerance, have been spotlighted in the field of the biomedical and health food additive industries [ 5 ]. The biological activity of AST is basically related to a hydroxyl group and a keto group on each end of its chemical structure; its peculiar features promote human health [ 6 , 7 ]. In particular, unique chemical structures enable it to scavenge reactive species of oxygen or nitrogen, i.e., polar end groups and double bonds of the middle segment are contributed to quench free radicals and remove high-energy electrons, respectively [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Astaxanthin occurs naturally either in unesterified (yeast) or esterified form (algae). In H. pluvialis it is found mainly in esterified form as monoester bound to short-chain fatty acids [19][20][21]. Approximately 70% of the astaxanthin pool of H. pluvialis with enzyme formation are monoesters, 25% diesters, and 5% free astaxanthin, predominantly in 3S,3S' form [22].…”
Section: Introductionmentioning
confidence: 99%
“…Astaxanthin has been quantified by various analytical methods, such as HPLC-DAD [8,12,16,18,21,23] and LC-(APCI)MS [24][25][26]. Castillo et al [27] focused on environmentally friendly solid phase dispersion (MSPD) extraction with ethanol, ethyl lactate and water where they obtained three new acids, determined some astaxanthin monoesters and no diester.…”
Section: Introductionmentioning
confidence: 99%